Nursing intervention and follow-up compliance after abnormal cervical cancer screening - Xiaohui Deng; Xiaoqing Pang; Zhengyan Dai (Medicine, 2026)
This study aimed to explore the impact of systematic nursing intervention on follow-up compliance among patients with abnormal cervical cancer screening results. This was a single-center, retrospective, time-grouped cohort study. A total of 182 patients who received cervical cancer screening at our hospital from June 2023 to June 2025 and had abnormal results requiring further follow-up were enrolled. According to the implementation timing of the nursing program, patients from June 2023 to May 2024 were included in the control group (routine nursing, 91 cases), and patients from June 2024 to June 2025 were included in the intervention group (systematic nursing intervention, 91 cases). The primary outcome was short-term follow-up compliance, defined as completion of colposcopy or treatment within 3 months after notification. Follow-up compliance rates, adherence levels, and reasons for loss to follow-up were compared. Univariate and multivariate logistic regression analyses were performed to explore influencing factors, and potential time-period bias was considered when interpreting the results. The follow-up compliance rate in the intervention group was 86.81%, significantly higher than that in the control group (64.84%) ( P < .001). Regarding reasons for loss to follow-up, the control group was primarily due to forgetting (34.38%) and fear/anxiety (25.00%), while the intervention group was mainly due to being busy with work (33.33%) and inconvenient transportation (25.00%) ( P = .026). Multivariate analysis showed that nursing intervention was independently associated with improved follow-up compliance (odds ratio [OR] = 4.128, P < .001); age ≥51 years (OR = 0.312, P = .010), education level of junior college or above (OR = 3.245, P = .014), and urban residence (OR = 2.436, P = .020) were also independent influencing factors. Subgroup analysis indicated that nursing intervention improved compliance rates across all populations, with more significant effects observed in human papillomavirus-positive and rural populations. Systematic nursing intervention was associated with improved short-term follow-up compliance among patients with abnormal cervical cancer screening results. Because this study used a retrospective cohort based on time grouping and was conducted in a single medical institution, the findings should be interpreted cautiously and applied primarily to similar clinical settings.